A rare case report of tissue infection caused by Pantoea piersonii (basionym Kalamiella piersonii) - Atilan, Kubra; Ozdem, Tayfun; Aydogan, Canset Nur; Hosbul, Tugrul (Folia microbiologica, 2025)
In 2019, Pantoea piersonii was initially isolated from the interior surfaces of the International Space Station. This microorganism is a species within the genus Pantoea in the family Erwiniaceae, belonging to the order Enterobacterales. Recent literature has documented four cases of its isolation. Despite initial predictions suggesting the non-pathogenicity of P. piersonii strains, evidence from observed cases indicates potential pathogenicity. According to documented evidence in the literature, this microorganism is capable of causing severe and life-threatening conditions, including sepsis. Traditional tests, as well as automated systems, may fail to provide complete differentiation due to these similarities. While MALDI-TOF MS is a valuable tool for identification in clinical diagnostic microbiology, sequencing may be necessary for precise identification. To determine the antibiotic susceptibility profile, various methods can be utilized, including minimum inhibitory concentration determination, disk diffusion testing (Kirby-Bauer test), genotypic resistance assays (PCR and sequencing), and automated systems. The literature reports a limited number of cases associating P. piersonii with human infection. This study contributes to this body of knowledge by reporting a novel case in which P. piersonii was isolated from a tissue sample for the first time. In this case report, the patient achieved recovery following the administration of appropriate antibiotic treatment based on the diagnosis. It underscores the need for precise identification and understanding of its pathogenicity.
Keywords: Microbial Sensitivity Tests; enterobakteriální infekce; mikrobiální testy citlivosti; Humans; mužské pohlaví; Anti-Bacterial Agents; lidé; Enterobacteriaceae Infections; antibakteriální látky; Male; Pantoea